Phase Transformation and Physical Properties of Al N-Co Film - Oh, C.S.; Kil, S.C.; Han, C.S. (Asian Journal of Chemistry, 2013)
Annealing techniques were applied to induce phase transformations and phase separations in Al N-Co thin films with various Co contents and Al N-Co multilayer thin films with various layer-thicknesses were prepared by a two-facing-target type DC sputtering system. X-ray diffraction and electron diffraction techniques were used to examine the behaviour of phase transformations and phase separations. The transmission electron microscopy was also used to evaluate the microstructure changes in the films. Magnetization and resistivity of the films were evaluated by vibration sample magnetometer and four-probe method respectively. It was found that magnetization and resistivity were sensitive to the phase transformations and phase separations as well as the changes in the microstructure of the films.